2013
DOI: 10.4322/polimeros.2013.093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma fluorination variables on the deposition and growth of partially fluorinated polymer over PMMA films

Abstract: Abstract:In this work, an investigation was made of the modification of film surface of Poly(methylmethacrylate) (PMMA) using the plasma polymerization technique. PMMA films 10 µm thick were obtained by Spin-Coating starting from a chloroform solution (15.36% w/w). The films were exposed to the plasma of CHF 3 at different gas pressures and exposure times to increase the thickness of fluorinated polymers onto PMMA films. The plasma fluorinated optical films were characterized by gravimetry, FTIR-ATR, contact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…As the sodium percentages are consistently higher than that of chlorine, other sodium-containing deposits are likely to be present. In previous works regarding gas fluorinated PMMA samples immersed in SAH (8 weeks), the EDS analysis indicated the presence of sodium chloride crystallites but a negligible calcium deposition [10,30]. This previous result could be attributed to the concentration of NaCl in the SAH being > ×50 higher than that calcium and phosphate.…”
Section: Immersion Studies Resultsmentioning
confidence: 81%
“…As the sodium percentages are consistently higher than that of chlorine, other sodium-containing deposits are likely to be present. In previous works regarding gas fluorinated PMMA samples immersed in SAH (8 weeks), the EDS analysis indicated the presence of sodium chloride crystallites but a negligible calcium deposition [10,30]. This previous result could be attributed to the concentration of NaCl in the SAH being > ×50 higher than that calcium and phosphate.…”
Section: Immersion Studies Resultsmentioning
confidence: 81%
“…Giacon et al [3] showed that thickness for the fluorinated film around 0.57 μm was suitable for cladding of PMMA with core of 14 μm. While Padilha et al [20] observed 0.61 μm of fluorinated polymer at 0.7 torr and 20 min. In this present work, PMMA films treated with plasma showed low roughness at this plasma condition.…”
Section: Resultsmentioning
confidence: 99%
“…Padilha et al [20] studied the effect of plasma treatment on the deposition of films fluorinated over PMMA, the results showed that films treated using CHF 3 plasma obtained acceptable thickness for optical devices. Under these conditions, a profilemeter analysis has been carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work [11] showed the feasibility to use the CF 4 + H 2 plasma polymerization to modify the surface and reduce the refractive index of PMMA. XPS and FTIR-ATR analysis revealed that a thin layer of a partially fluorinated polymer was deposited on the PMMA films after plasma [12].…”
Section: Introductionmentioning
confidence: 99%
“…The cladding was a fluorinated polymer (0.6 m) produced by CHF 3 plasma polymerization (parallel plate reactor, 13.56 MHz) deposited under experimental conditions similar to those used in our previous work [12] and the core was a PMMA optical film (14 m) prepared by spin coating. The refractive index of the fluorinated film was characterized by ellipsometry and metricon prism coupler.…”
Section: Introductionmentioning
confidence: 99%